Psychometric Validation of the Spanish Gaming Disorder Test (GDT): Item Response Theory and Measurement Invariance Analysis. - Maldonado-Murciano, Laura; Pontes, Halley M.; Barrios, Maite; Gómez-Benito, Juana; Guilera, Georgina (International Journal of Mental Health & Addiction, 2023)
Gaming Disorder (GD) has been recently added to the eleventh revision of the International Classification of Diseases (ICD-11) by the World Health Organization (WHO), as such, psychometrically sound psychological measures are required to assess this disorder. The objective of this study was to investigate the psychometric properties of the Spanish Gaming Disorder Test (GDT) by assessing its dimensionality, reliability, convergent validity, and associations with other variables of importance through polytomous Item Response Theory (IRT) and Measurement Invariance (MI) analysis across genders. To achieve this, a sample of 538 gamers (42.94% female, mean = 23.29 years, SD = 7.24) was recruited. The results obtained supported a one-factor structure for the Spanish GDT with adequate reliability and convergent validity. Furthermore, satisfactory goodness of fit in the partial credit model (PCM) with more precise scores at high trait levels to assess GD was found, and strict invariance across genders was supported. These findings attest to the suitability of the Spanish GDT for clinical assessment and research on disordered gaming beyond community samples.